Hubungan Tingkat Stres dan Perilaku Konsumsi Makanan Cepat Saji terhadap Kejadian Dismenore - Nurmala Sari; Rifa Yanti; Rika Ruspita; Fajar Sari Tanberika (LPPM Universitas Bhamada Slawi PSDKU D III Kebidanan Kampus Kota Pekalongan, 2026)
Adolescents experience emotional, psychosocial, and sexual development marked by menstruation. Dysmenorrhea is a common complaint among adolescent girls. Suspected contributing factors include the consumption of fast food, which is high in fat, sugar, and calories but low in fiber, and may affect progesterone metabolism. In addition, stress increases cortisol production, which disrupts the balance of reproductive hormones and may increase the risk of dysmenorrhea. This quantitative study used a cross-sectional design. The sample consisted of female students at SMAN 1 Rimba Melintang selected by simple random sampling (n = 66). Data were collected using a dysmenorrhea questionnaire, the PSS-10, and a fastfood consumption frequency questionnaire. Chi-square test results showed a significant relationship between fast food consumption and dysmenorrhea (p = 0.03; OR = 5.0) and between stress level and dysmenorrhea (p = 0.05; OR = 6.4). This study aimed to examine the relationship between stress level and fastfood consumption behavior with the occurrence of dysmenorrhea among adolescent girls at SMAN 1 Rimba Melintang, Rokan Hilir Regency. The findings are expected to provide a basis for designing promotive and preventive efforts to improve adolescent reproductive health, especially through stress management and the adoption of healthier eating patterns.